Cytokine levels in healthy and allergic mothers and their children during the first year of life - Prokesová, Ludmila; Lodinová-Zádníková, Raja; Zizka, Jan; Kocourková, Ingrid; Novotná, Olga; Petrásková, Petra; Sterzl, Ivan (Pediatric allergy and immunology, 2006)
To assess the regulatory changes of immune system in children genetically pre-disposed to allergic diseases and in their mothers, we tested cytokines IL-4, IL-5, IL-6, IL-10, IL-13, IFN-gamma and TGF-beta in 21 healthy and 21 allergic mothers (serum at the time of delivery, colostrum and milk throughout the suckling period) and their children (cord blood, venous blood and stool filtrates) up to 1 yr of age. Samples were taken at the time of delivery, 4 days post-partum and then after 3, 6 and 12 months. Significant differences between the healthy and the allergic group were found in the levels of IL-4, IL-10, IL-13 and IFN-gamma. The levels of IL-4 in the allergic group were generally higher; the levels in the sera of children of allergic mothers during the post-natal life decreased, reaching levels typical for the healthy group at 1 yr of age. Allergic mothers exhibited markedly higher IL-10 levels in the serum at the time of delivery and in milk 3 months after delivery than healthy mothers while after 6 months the IL-10 levels in all samples from the allergic group were very low. Children from allergic group had lower intestinal content of IL-13 in comparison with the healthy counterparts. At 1 yr of age, the levels of IFN-gamma in sera and stool of children from the allergic group sharply increased. TGF-beta levels in the sera of both groups were high, while in the milk they were relatively low and substantially lower that in the children's stool. TGF-beta of mammary secretions is therefore unlikely to exert a decisive regulatory influence on the children's immunity. Long-term clinical monitoring of the children will be performed to evaluate the potential prognostic significance of these changes for the future development of allergies.
Keywords: interferon gama; Feces; Interferon-gamma; interleukin-13; Colostrum; Interleukin-4; těhotenství; kojenec; alergie; Milk, Human; cytokiny; Infant; interleukin-10; Fetal Blood; Cytokines; Breast Feeding; interleukin-4; Infant, Newborn; ženské pohlaví; novorozenec; mateřské mléko; feces; Humans; Interleukin-13; Pregnancy; kojení; kolostrum; Interleukin-10; Female; fetální krev; lidé; Hypersensitivity